Study of the characteristics of the developed barker-like codes - Kutsyk, Oleg; Riznyk, Oleg (Комп’ютерне моделювання та інформаційні технології, 2023)
The synthesis of non-periodic signals with correlation properties, which have a linear structure of the spectrum and provide unequivocal measurement and high resolution, is relevant. Signals that satisfy this condition are called signals with the "no more matches" property. The main requirement for signals with a selected compression ratio is the minimization of autocorrelation side lobes.Among the most well-known and more frequently used signals in practice can be noted: Barker codes, M‑sequences (Huffman codes), multiphase Frank codes, linear– and V‑figuratively frequency modulated signals.